Keberanian Ratu Wasti: Reinterpretasi Ester 1:1-22 Dari Perspektif Teologi Tubuh - Mangore, Sundriati; Thomas, Art (Jurnal Ilmiah Wahana Pendidikan, 2024)
Destination study this is study about courage Queen Vhasti so that he brave against king Ahasuerus as well as effort reinterpretation of Esther 1:1-22 of perspective theology body. Study this is study qualitative with studies library, because what becomes focus study researcher is on text Bible with use method Hermeneutics feminist investigation. Data collected through related literature and references with who Queen Vhasti this, how the great power of king Ahasuerus power at the moment that, as well as how theology body looking at the queen's fight Vhasti against the king at once her husband in Esther 1:1-22. From the results: Vhasti is pioneer from courage all woman. Eligible women life on the decision alone, and not depend on decision men. Because there more law tall from king's law law culture that says that woman no can displayed in front general.